Surgical treatment of flat feet - Ruiz de Marella, Selva (Cirugía del Uruguay, 1973)
In children between the ages of eight and fourteen, in whom arch supports have failed, a surgical therapy is suggested. It is important to restore heel alignment, correcting its va!gus and pronation (interna! rotation), is well to correct the longitudinal arch. The operation is performed on tendons and capsular structures, without any arthrodesis. The lengthening of the tendo calcaneous is a preliminary procedure aimed at freeing the heel for its rea!ignment. The anterior tibial tendon is transferred, rerouting it without disinsertion and passing it through an osteotomy and a slot in the navicular end; the posterior tibia! tendon which had previously been dissected from its insertion, is reattached. For eight weeks a cast is applied. Walking is not permitted until then.